2013
DOI: 10.1071/wf11115
|View full text |Cite
|
Sign up to set email alerts
|

Social science research related to wildfire management: an overview of recent findings and future research needs

Abstract: As with other aspects of natural-resource management, the approach to managing wildland fires has evolved over time as scientific understanding has advanced and the broader context surrounding management decisions has changed. Prior to 2000 the primary focus of most fire research was on the physical and ecological aspects of fire; social science research was limited to a small number of studies. However, as more people moved into fire-prone areas interest grew in understanding relevant social dynamics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
134
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(145 citation statements)
references
References 67 publications
4
134
0
7
Order By: Relevance
“…For instance, local information seeking and public information dissemination influence both locally specific risk perception (Brenkert-Smith et al 2013) and wildfire preparedness actions (McCaffrey 2004). Recent social science literature related to wildfire demonstrates a clear relationship between risk perception, public communication, information seeking and preparedness actions, but less knowledge exists on the effects of prefire interaction and incident communication with local residents (McCaffrey et al 2013a). Our study addresses a significant gap in communication literature examining how to integrate geographically specific threat indices into public information dissemination efforts, establishing whether information-seeking patterns in southern California mirror information-seeking patterns in other areas, and by considering renters as well as homeowners in our study.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, local information seeking and public information dissemination influence both locally specific risk perception (Brenkert-Smith et al 2013) and wildfire preparedness actions (McCaffrey 2004). Recent social science literature related to wildfire demonstrates a clear relationship between risk perception, public communication, information seeking and preparedness actions, but less knowledge exists on the effects of prefire interaction and incident communication with local residents (McCaffrey et al 2013a). Our study addresses a significant gap in communication literature examining how to integrate geographically specific threat indices into public information dissemination efforts, establishing whether information-seeking patterns in southern California mirror information-seeking patterns in other areas, and by considering renters as well as homeowners in our study.…”
Section: Introductionmentioning
confidence: 99%
“…As wildfires increasingly intersected with the wildland-urban interface interest grew in understanding the role of social science dynamics. McCaffrey et al (2013) have reviewed the development of human dimensions of wildland fire, including the social acceptability of fire and fuels management, public responses during fires and post-fire recovery. The review was based in grounded theory that identified conceptual categories and their relationships (Glaser and Strauss 1967).…”
Section: Social Issues Of Fire Sciencementioning
confidence: 99%
“…The need to expand and integrate the spatial and temporal scope of fire and fuels research and analysis is perhaps the theme with broadest applicability (e.g. Hyde et al 2013;McCaffrey et al 2013;Miller and Ager 2013;Robichaud and Ashmun 2013).…”
Section: Themesmentioning
confidence: 99%
“…An important research area is the influence of institutions (e.g., policy) and associated processes (policy evolution) on wildfire management flexibility and behavior (Busenburg 2004, Stephens and Ruth 2005, Steelman and Burke 2007, McCaffrey et al 2013. Institutions are the systems of established and prevalent social rules that structure human decision making and behavior within social groups and in relation to the natural world (Ostrom 1990, North 1990, Crawford and Ostrom 1995, Helmke and Levitsky 2004, Hodgson 2006.…”
Section: Introductionmentioning
confidence: 99%